An alternative method toward educational reform in Turkey in the light of Said Nursi Badiuzzaman (1876-1960) - Abdul Rahim, Adibah (2017)
This paper attempts at studying the prominent Muslim scholar in Turkey, Said Nursi Badiuzzaman’s proposal for educational reform and his alternative method to the old educational system in Turkey during his time. During the time of Nursi, Turkey had been heavily influenced by secularism under the leadership of Kamal al Tartuk. The religious values had been marginalized from the practical aspects of man’s life. At the same time, the Muslims world had been dominated by the West in science and technology giving them the strength to control the economic power of the world. This domination had challenged the Muslims intellectually, spiritually and morally. It led to the weak conditions of Muslims. Said Nursi observed that those problems of Muslim could be solved through the educational reform program. He criticized the prevalent educational system in Turkey at that time was not able to produce a balance personality of Muslims as well as failed to achieve a progress in society. Therefore, the system of education, according to him, must be reoriented accordingly. He proposed for a restructure of the curriculum in order to be aligned with the requirements of Islam and adjusted with the requirements of modern time. Although Nursi’s idea of educational reform was aimed at every level including primary level, secondary level, and university level, he gave emphasis on the university level. This paper did not only examine the theoretical dimensions of his educational reform but also highlighted the practical applications of the process.